Play like you mean it : passion, laughs, and leadership in the world's most beautiful game - Ryan, Rex. (Doubleday, 2011)
The head coach of the New York Jets shares the lessons he has learned in leadership and motivation throughout his career, recounting colorful stories from his work with the Jets and the Ravens as well as memories about his father, NFL coach Buddy Ryan.